2016
DOI: 10.1186/s12936-016-1609-7
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers adherence to referral guidelines: evidence from studies introducing RDTs in two malaria transmission settings in Uganda

Abstract: BackgroundMany malaria-endemic countries have implemented national community health worker (CHW) programmes to serve remote populations that have poor access to malaria diagnosis and treatment. Despite mounting evidence of CHWs’ ability to adhere to malaria rapid diagnostic tests (RDTs) and treatment guidelines, there is limited evidence whether CHWs adhere to the referral guidelines and refer severely ill children for further management. In southwest Uganda, this study examined whether CHWs referred children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
5
2
Order By: Relevance
“…This does not match with evidence from another study (36). Additional factors on our experience and reported in the literature are logistics, finances of the patients, communication skills, perceived quality of care, lack of time and need to care for other children and an improvement in the child's condition (36,38,40,41).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This does not match with evidence from another study (36). Additional factors on our experience and reported in the literature are logistics, finances of the patients, communication skills, perceived quality of care, lack of time and need to care for other children and an improvement in the child's condition (36,38,40,41).…”
Section: Discussioncontrasting
confidence: 73%
“…RAS administration was significantly associated with increased odds of completing referral, which is similar with result from another study in Uganda (37).This may be explained in our study by the sensitization of caretakers and health worker during trainings prior to RAS rollout. However, our findings were different from another study in Uganda, which found that nearly all children treated with pre-referral RAS failed to comply with referral (38). Transport did not show an association with referral completion; eight in ten caretakers went by foot to a RHF, which was consistent with results from a study conducted in Afghanistan, where the majority of caretaker successfully completed referral by foot (39).…”
Section: Discussioncontrasting
confidence: 73%
“…The findings from these studies in Uganda and elsewhere show that community based referral systems operate less than optimally at each stage of the referral process. In the first stage, CHW often do not refer children with referral signs and symptoms to the nearest health centre [ 23 , 33 , 34 ]. In the second stage, caregivers often fail to comply with CHW referral advice and do not seek care from health centres [ 13 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of referral notes might have affected the continuity of care as information was not forwarded [27,28]. Non-adherence to referral guidelines was also observed among community health workers in Uganda [29] and Ghana [30] while a reasonable number of referrals supported with referral slips was observed among community health workers in Pakistan [27]. Most caregivers were advised on home-based sick child care and continued feeding.…”
Section: Plos Onementioning
confidence: 99%